Lithium iron phosphate material, preparation method thereof and lithium ion battery
By using hydroxyferric phosphate and doped hydroxyferric phosphate as phosphorus sources, combined with multi-level particle size design and sintering process, the capacity and resistivity problems of lithium iron phosphate materials have been solved, improving the performance of lithium-ion batteries and making them suitable for electric vehicles and energy storage systems.
Patent Information
- Application Number
- CN202511360780.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-22
- Publication Date
- 2025-10-28
- Estimated Expiration
- 2045-09-22
AI Technical Summary
Existing lithium iron phosphate materials suffer from problems such as insufficient capacity utilization, high resistivity, and poor cycle life during preparation, which seriously restrict the performance upgrade of lithium-ion batteries.
Using hydroxyferric phosphate and hydroxyferric phosphate containing metal dopants as phosphorus sources, lithium iron phosphate materials were prepared through a four-stage particle size distribution design, combined with wet grinding and multiple sintering, which improved electronic conductivity and lithium-ion transport efficiency and suppressed interparticle melting.
It significantly improves the compaction density, energy density, rate performance, and cycle life of lithium iron phosphate materials, meeting the requirements of long-range electric vehicles and high-efficiency energy storage systems.
Smart Images

Figure CN120841482A_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to a lithium iron phosphate material and its preparation method, and a lithium-ion battery. Background Technology
[0002] Lithium iron phosphate (LiFePO4) is a mainstream cathode material for lithium-ion batteries, possessing characteristics such as high theoretical capacity, good thermal stability, and low cost, and is widely used in power batteries and energy storage. Increasing the compaction density of the cathode material can effectively improve the volumetric energy density of lithium-ion batteries, meeting the demands of end-user applications for long driving ranges. Existing preparation processes mainly synthesize high-compact-density lithium iron phosphate materials through solid-state methods, liquid-state methods, and carbothermal reduction methods. However, lithium iron phosphate materials prepared by existing processes still suffer from insufficient capacity utilization, high resistivity, and poor cycle life, severely restricting battery performance upgrades. Summary of the Invention
[0003] The purpose of this disclosure is to provide a lithium iron phosphate material with improved electrical performance, a method for preparing the same, and a lithium-ion battery.
[0004] To achieve the above objectives, the first aspect of this disclosure provides a method for preparing lithium iron phosphate material, the method comprising: The first mixture containing the first iron phosphorus source, the first lithium phosphorus source, the first metal dopant and the first carbon source is wet-milled, dried and then sintered to obtain the first precursor. The second mixture containing the second iron phosphorus source, the second lithium phosphorus source, the second metal dopant, and the second carbon source is wet-milled, dried, and then subjected to a second sintering to obtain the second precursor. The third mixture containing the first precursor and the third carbon source is wet-milled to obtain a first slurry with a first particle size. The fourth mixture containing the first precursor and the fourth carbon source is wet-milled to obtain a second slurry with a second particle size. The fifth mixture containing the second precursor and the fifth carbon source is wet-milled to obtain a third slurry with a third particle size. The sixth mixture containing the second precursor and the sixth carbon source is wet-milled to obtain a fourth slurry with a fourth particle size. The seventh mixture containing the first slurry, the second slurry, the third slurry, and the fourth slurry is dried and then subjected to a third sintering to obtain lithium iron phosphate material; Wherein, the first iron phosphorus source is hydroxyferric phosphate, and the second iron phosphorus source is hydroxyferric phosphate containing metal doping elements; the first particle size, the second particle size, the third particle size, and the fourth particle size decrease sequentially.
[0005] Optionally, the iron-phosphorus molar ratio of the first phosphorus-iron source is 1.40~1.46, and the BET specific surface area is 4~50 m². 2 / g.
[0006] Optionally, the iron-to-phosphorus molar ratio of the second phosphorus-iron source is 1.44~1.50, and the BET specific surface area is 30~100 m². 2 / g.
[0007] Optionally, the metal doping element includes at least one of Ti, Nb, V, Mn, Mg, Ni and Zr.
[0008] Optionally, based on the total weight of the second iron phosphorus source, the content of the metal doping element in the second iron phosphorus source is 0.1~0.4wt%.
[0009] Optionally, the first lithium phosphorus source and the second lithium phosphorus source each independently include at least one of lithium phosphate, lithium hydrogen phosphate, and lithium dihydrogen phosphate; The first metal dopant includes at least one of manganese dopant, vanadium dopant, nickel dopant, and zirconium dopant; The second metal dopant includes at least one of titanium dopant, niobium dopant, and magnesium dopant; The first supplement and the second supplement each independently comprise at least one of phosphoric acid, ammonium dihydrogen phosphate, lithium carbonate, lithium hydroxide, lithium acetate, and lithium oxalate; The first carbon source, the second carbon source, the third carbon source, the fourth carbon source, the fifth carbon source, and the sixth carbon source each independently include at least one of glucose, sucrose, polyethylene glycol, citric acid, polyvinylpyrrolidone, and starch.
[0010] Optionally, the first metal dopant includes at least one of manganese acetate, ammonium metavanadate, nickel oxide, and zirconium oxide; The second metal dopant includes at least one of titanium dioxide, niobium oxide, and magnesium acetate.
[0011] Optionally, the first mixture further contains a first supplement, and the second mixture further contains a second supplement; The first supplement and the second supplement each independently comprise at least one of phosphoric acid, ammonium dihydrogen phosphate, lithium carbonate, lithium hydroxide, lithium acetate, and lithium oxalate.
[0012] Optionally, based on the total weight of the first precursor, the carbon content of the first precursor is 0.1~0.3wt%, and the metal doping content is 0.1~0.5wt%. Based on the total weight of the second precursor, the carbon content of the second precursor is 0.1~0.3wt%, and the metal doping content is 0.1~0.7wt%.
[0013] Optionally, in the third mixture, the weight ratio of the first precursor to the third carbon source is 1000:(30~60). In the fourth mixture, the weight ratio of the first precursor to the fourth carbon source is 1000:(30~60). In the fifth mixture, the weight ratio of the second precursor to the fifth carbon source is 1000:(30~60). In the sixth mixture, the weight ratio of the second precursor to the sixth carbon source is 1000:(30~60).
[0014] Optionally, the first particle size is 1.0~2.0 μm, the second particle size is 0.5~1.0 μm, the third particle size is 0.2~0.5 μm, and the fourth particle size is 0.1~0.2 μm; and / or, In the seventh mixture, the weight ratio of the first slurry, the second slurry, the third slurry and the fourth slurry is 1:(0.5~1):(0.25~1):(0.25~1).
[0015] Optionally, the conditions for the first sintering include: a temperature of 800~840℃ and a time of 4~10h; The conditions for the second sintering include: a temperature of 600~700℃ and a time of 3~5h; The conditions for the third sintering include: a temperature of 750~800℃ and a time of 4~8h.
[0016] A second aspect of this disclosure provides a lithium iron phosphate material prepared by the method described in the first aspect of this disclosure.
[0017] In a third aspect, this disclosure provides a lithium-ion battery comprising the lithium iron phosphate material described in the second aspect of this disclosure.
[0018] Through the above technical solutions, this disclosure utilizes hydroxyferric phosphate and hydroxyferric phosphate containing metal dopants as phosphorus iron sources to prepare two precursors, improving the electronic conductivity and lithium-ion transport efficiency of lithium iron phosphate materials. It also suppresses interparticle coalescence during secondary sintering and effectively enhances the compaction density of lithium iron phosphate materials based on a four-level particle size distribution design, while ensuring efficient capacity utilization. Using this lithium iron phosphate material to prepare lithium-ion batteries can significantly improve the battery's energy density, rate performance, and cycle life, meeting the development needs of high-end application markets such as long-range electric vehicles and high-efficiency energy storage systems, and possessing promising prospects for industrial application.
[0019] Other features and advantages of the present disclosure will be described in detail in the following detailed description. Attached Figure Description
[0020] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following detailed description, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings: Figure 1 This is an electron microscope image of the lithium iron phosphate material prepared in Example 1. Detailed Implementation
[0021] The following describes the specific embodiments of the present disclosure in detail with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure and are not intended to limit the present disclosure.
[0022] According to a first aspect of this disclosure, a method for preparing lithium iron phosphate material is provided, the method comprising the following steps S1 to S7: S1. The first mixture containing the first iron phosphorus source, the first lithium phosphorus source, the first metal dopant and the first carbon source is wet-milled, dried and then sintered to obtain the first precursor. S2. The second mixture containing the second phosphorus iron source, the second phosphorus lithium source, the second metal dopant, the second carbon source, and the optional second additive is wet-milled, dried, and then subjected to a second sintering to obtain the second precursor. S3. The third mixture containing the first precursor and the third carbon source is wet-milled to obtain a first slurry with a first particle size. S3. The fourth mixture containing the first precursor and the fourth carbon source is wet-milled to obtain a second slurry with a second particle size. S5. The fifth mixture containing the second precursor and the fifth carbon source is wet-milled to obtain a third slurry with a third particle size. S6. The sixth mixture containing the second precursor and the sixth carbon source is wet-milled to obtain a fourth slurry with a fourth particle size. S7. The seventh mixture containing the first slurry, the second slurry, the third slurry and the fourth slurry is dried and then subjected to a third sintering to obtain lithium iron phosphate material; Wherein, the first iron phosphorus source is hydroxyferric phosphate, and the second iron phosphorus source is hydroxyferric phosphate containing metal doping elements; the first particle size, the second particle size, the third particle size, and the fourth particle size decrease sequentially.
[0023] This disclosure uses two different doping systems of phosphorus iron source as raw materials to prepare precursors, which is beneficial to improve the electronic conductivity and lithium-ion transport efficiency of lithium iron phosphate materials, and can suppress interparticle melting during secondary sintering. Based on the four-level particle size distribution design, it effectively improves the compaction density of lithium iron phosphate materials, while ensuring efficient capacity utilization.
[0024] In step S1, a first precursor is prepared using hydroxyferric phosphate as the first phosphorus iron source. This first precursor is used in subsequent steps to prepare a first slurry with the largest particle size (i.e., the first particle size) and a second slurry with a medium particle size (i.e., the second particle size).
[0025] The general chemical formula of this ferric hydroxyphosphate can be Fe. x (PO4)(OH)·nH2O, where x is 1.4~1.5. In one specific embodiment, the iron-phosphorus molar ratio (Fe / P) of the first phosphorus iron source can be 1.40~1.46, and the BET specific surface area can be 4~50 m². 2 / g.
[0026] This ferric hydroxyphosphate can be prepared by a co-precipitation method. In one specific embodiment, the preparation steps of this ferric hydroxyphosphate may include: (1) Ferrous sulfate, a byproduct of titanium dioxide, phosphorus source and precipitant are mixed and purified by pressure filtration to obtain ferrous sulfate solution; (2) Add an appropriate amount of phosphoric acid to the ferrous sulfate solution to lower the pH value of the ferrous sulfate solution to 2~2.5; (3) Add hydrogen peroxide, phosphoric acid, ammonium dihydrogen phosphate solution and ammonia to ferrous sulfate solution and react at 25~70℃ for 2~6h to form a mixed slurry. Then wash and filter with water multiple times to obtain hydroxyferric phosphate precursor. (4) The above-mentioned hydroxyferric phosphate precursor was flash-dried at an inlet air temperature of 220±20℃ and an outlet air temperature of 110±10℃, and sintered at 530~560℃ for 4~5h in an air atmosphere to obtain hydroxyferric phosphate.
[0027] The first lithium phosphorus source is a compound containing phosphorus and lithium. The lithium-phosphorus molar ratio (Li / P) of the first lithium phosphorus source can be 1 to 3. Specifically, the first lithium phosphorus source can include at least one of lithium phosphate (Li3PO4), lithium dihydrogen phosphate (LiH2PO4), and lithium hydrogen phosphate (Li2HPO4). The amount of the first lithium phosphorus source can be adjusted within a certain range. Specifically, the molar ratio of the first lithium phosphorus source (calculated as Li) to the first iron phosphorus source (calculated as Fe) can be 1.00 to 1.05, preferably 1.01 to 1.05. The first lithium phosphorus source preferably has a high purity (e.g., above 98%) to improve the quality of lithium iron phosphate materials.
[0028] The first metal dopant may include at least one of manganese dopant, vanadium dopant, nickel dopant, and zirconium dopant. Introducing these metal dopant types is beneficial for further improving the discharge plateau and rate performance of large and medium-sized particles in lithium iron phosphate materials. It also helps improve the roundness of large and medium-sized particles after secondary sintering, thereby further increasing the compaction density of the lithium iron phosphate material. Specifically, the first metal dopant may include at least one of manganese acetate (Mn(CH3COO)2), ammonium metavanadate (NH4VO3), nickel oxide (NiO), and zirconium oxide (ZrO2). The amount of the first metal dopant can be adjusted within a certain range to ensure that the first precursor has a suitable first metal doping content. Specifically, based on the total weight of the first precursor, the metal doping content of the first precursor (including the metal doping content introduced by the first metal dopant) can be 0.1~0.5wt%, preferably 0.3~0.4wt%.
[0029] The first carbon source may include at least one of glucose, sucrose, polyethylene glycol (PEG), citric acid, polyvinylpyrrolidone (PVP), and starch. Using a lower amount of the first carbon source is beneficial for obtaining a high-quality precursor with higher crystallinity, more regular morphology, and more concentrated size distribution. The resulting first precursor has a lower carbon content; specifically, based on the total weight of the first precursor, the carbon content can be 0.1~0.3 wt%.
[0030] The first mixture may also contain a first supplement, which may include at least one of a phosphorus-containing compound and a lithium-containing compound, used to balance the elemental stoichiometry in the finished product and improve the purity of the material. Specifically, the first supplement may include at least one of phosphoric acid (H3PO4), ammonium dihydrogen phosphate (NH4H2PO4), lithium carbonate (Li2CO3), lithium hydroxide (LiOH), lithium acetate (CH3COOLi), and lithium oxalate (Li2C2O4), preferably including at least one of phosphoric acid and lithium carbonate. The amount of the first supplement can be adjusted as needed to give the obtained first precursor a suitable phosphorus-iron-lithium molar ratio. Specifically, the phosphorus-iron-lithium molar ratio (P / Fe / Li) of the first precursor may be 1:(0.950~0.970):(0.960~1.019).
[0031] The liquid medium used in wet grinding can include at least one of deionized water and anhydrous ethanol. Specifically, the conditions for wet grinding can include: a temperature of 10~45℃, a grinding particle size D50 of 0.7~0.9μm, and a solid content of 30~50wt%.
[0032] Drying can be spray drying. Specifically, drying conditions may include: inlet temperature of 180~240℃, outlet temperature of 80~140℃, particle size D50 of 20~60μm, and moisture content ≤1.5wt%.
[0033] The first sintering can be carried out in the presence of a protective gas, which may include at least one of nitrogen and argon. Specifically, the conditions for the first sintering may include a temperature of 800~840℃ and a time of 4~10h. Further, after the first sintering, the first precursor particles can be obtained by an airflow pulverization step.
[0034] In step S2, a second precursor is prepared using hydroxyferric phosphate containing metal dopant as a second iron phosphorus source. This second precursor is used in subsequent steps to prepare a third slurry with a medium particle size (i.e., a third particle size) and a fourth slurry with a minimum particle size (i.e., a fourth particle size).
[0035] This metal-doped hydroxyferric phosphate can be an in-situ interstitial doped type, a composite phosphorus-iron source formed by the metal dopant embedding itself into the crystal lattice as interstitial atoms or substitutional atoms during the crystallization process of the hydroxyferric phosphate matrix. Using this metal-doped hydroxyferric phosphate as a second phosphorus-iron source has two advantages: firstly, it can construct an ordered and stable doped metal-iron-phosphorus oxygen framework in the precursor stage, improving the electronic conductivity and lithium-ion transport efficiency of lithium iron phosphate materials, and suppressing lithium-iron ion mixing defects during secondary sintering, thereby refining grains and controlling grain growth morphology. Secondly, because it belongs to a different doping system than the first phosphorus-iron source, it can suppress interparticle fusion during secondary sintering, allowing the final product to maintain particle independence and a predetermined particle size distribution while achieving high crystallinity. This solves the performance degradation problem caused by severe particle sintering in traditional high-density materials.
[0036] The second iron-phosphorus source can have a high iron-phosphorus molar ratio and specific surface area to prepare medium and small particles with a high iron-phosphorus molar ratio, thereby improving the theoretical specific capacity of the material. Specifically, the iron-phosphorus molar ratio (Fe / P) of the second iron-phosphorus source can be 1.44~1.50, and the BET specific surface area can be 30~100m². 2 / g. The metal doping element may include at least one of Ti, Nb, Mn, Mg, Ni and Zr, preferably at least one of Ti and Nb; further, based on the total weight of the second phosphorus iron source, the content of the metal doping element in the second phosphorus iron source is 0.1~0.4wt%. The ferric hydroxyphosphate containing metal dopant can be prepared by co-precipitation. In one specific embodiment, the preparation steps of the ferric hydroxyphosphate containing metal dopant may include: (1) Ferrous sulfate, a byproduct of titanium dioxide, phosphorus source and precipitant are mixed and purified by pressure filtration to obtain ferrous sulfate solution; (2) Add an appropriate amount of phosphoric acid to the ferrous sulfate solution to lower the pH value of the ferrous sulfate solution to 2~2.5; (3) Add doped metal oxide, hydrogen peroxide, phosphoric acid, ammonium dihydrogen phosphate solution and ammonia to ferrous sulfate solution and react at 25~70℃ for 2~6h to form a mixed slurry. Then wash and filter with water multiple times to obtain metal element doped hydroxy ferric phosphate precursor. (4) The above-mentioned hydroxyferric phosphate precursor was flash-dried at an inlet air temperature of 220±20℃ and an outlet air temperature of 110±10℃, and sintered at 530~560℃ for 4~5h in an air atmosphere to obtain hydroxyferric phosphate containing metal dopants.
[0037] The lithium-to-phosphorus molar ratio (Li / P) of the second lithium-phosphorus source can be 1 to 3. Specifically, the second lithium-phosphorus source can include at least one of lithium phosphate, dilithium hydrogen phosphate, and lithium dihydrogen phosphate, preferably at least one of lithium phosphate and dilithium hydrogen phosphate. The amount of the second lithium-phosphorus source can be adjusted within a certain range. Specifically, the molar ratio of the second lithium-phosphorus source (calculated as Li) to the second iron-phosphorus source (calculated as Fe) can be 1.0 to 1.1, preferably 1.03 to 1.08. The second lithium-phosphorus source preferably has a high purity (e.g., above 98%) to improve the quality of lithium iron phosphate materials.
[0038] The second metal dopant may include at least one of titanium dopant, niobium dopant, and magnesium dopant. Introducing such metal dopant is beneficial for refining grains and suppressing excessive grain growth during the secondary sintering process. Specifically, the second metal dopant may include at least one of titanium dioxide (TiO2), niobium oxide (Nb2O5), and magnesium acetate (Mg(CH3COO)2). The amount of the second metal dopant can be adjusted within a certain range to ensure that the second precursor has a suitable second metal doping content. Specifically, based on the total weight of the second precursor, the metal doping content of the second precursor (including the total metal doping content introduced by the second phosphorus iron source and the second metal dopant) can be 0.1~0.7wt%, preferably 0.5~0.6wt%.
[0039] The second carbon source may include at least one of glucose, sucrose, polyethylene glycol, citric acid, polyvinylpyrrolidone, and starch. The amount of the second carbon source can be adjusted within a low range to give the resulting second precursor a low carbon content; specifically, based on the total weight of the second precursor, the carbon content of the second precursor is 0.1 to 0.3 wt%.
[0040] The second mixture may also contain a second supplement, which may include at least one of a phosphorus-containing compound and a lithium-containing compound. Specifically, the second supplement may include at least one of phosphoric acid, ammonium dihydrogen phosphate, lithium carbonate, lithium hydroxide, lithium acetate, and lithium oxalate, preferably at least one of phosphoric acid and lithium carbonate. The amount of the second supplement may be adjusted as needed to give the resulting second precursor a suitable phosphorus-iron-lithium molar ratio. Specifically, the phosphorus-iron-lithium molar ratio (P / Fe / Li) of the second precursor may be 1:(0.970~1.000):(0.999~1.080).
[0041] The liquid medium used in wet grinding can include at least one of deionized water and anhydrous ethanol. Specifically, the conditions for wet grinding can include: a temperature of 10~45℃, a grinding particle size D50 of 0.2~0.4μm, and a solid content of 30~50wt%.
[0042] Drying can be spray drying. Specifically, drying conditions may include: inlet temperature of 180~240℃, outlet temperature of 80~140℃, particle size D50 of 20~60μm, and moisture content ≤1.5wt%.
[0043] The second sintering can be carried out in the presence of a protective gas, which may include at least one of nitrogen and argon. Specifically, the conditions for the second sintering may include a temperature of 600-700°C and a time of 3-5 hours. Further, after the second sintering, second precursor particles can be obtained through an airflow pulverization step.
[0044] In steps S3 to S6, the two precursors obtained in the above steps are wet-milled with a carbon source to prepare four slurries with specific target particle sizes.
[0045] The third, fourth, fifth, and sixth carbon sources can each independently include at least one of glucose, sucrose, polyethylene glycol, citric acid, polyvinylpyrrolidone, and starch; preferably, they include two of glucose, sucrose, polyethylene glycol, and polyvinylpyrrolidone. The amount of each carbon source (i.e., the third to sixth carbon sources) can be higher than that used in the preparation of the precursor, which not only helps to form a complete and dense carbon coating layer during final sintering, but also helps to maintain particle size distribution, improve compaction density and capacity, construct a multi-dimensional composite conductive network, and reduce internal resistance.
[0046] Specifically, in the third mixture, the weight ratio of the first precursor to the third carbon source can be 1000:(30~60). In the fourth mixture, the weight ratio of the first precursor to the fourth carbon source can be 1000:(30~60). In the fifth mixture, the weight ratio of the second precursor to the fifth carbon source can be 1000:(30~60). In the sixth mixture, the weight ratio of the second precursor to the sixth carbon source can be 1000:(30~60).
[0047] The liquid medium used in wet grinding can include at least one of deionized water and anhydrous ethanol. Specifically, the conditions for wet grinding can include a temperature of 10~45℃ and a solid content of 30~50wt%.
[0048] The particle size of the solid phase material in the first, second, third, and fourth slurries decreases sequentially. In one specific embodiment, the first particle size can be 1.0~2.0 μm, preferably 1.0~1.4 μm; the second particle size can be 0.5~1.0 μm, preferably 0.5~0.7 μm; the third particle size can be 0.2~0.5 μm, preferably 0.3~0.4 μm; and the fourth particle size can be 0.1~0.2 μm. The above particle size distribution scheme can significantly improve the bulk density and construct an excellent electrochemical active network, achieving ultra-high volumetric energy density while also ensuring high capacity utilization, low internal resistance, and good rate performance.
[0049] In step S7, the ratio of the first slurry, the second slurry, the third slurry, and the fourth slurry can be adjusted within a certain range. In one specific embodiment, the weight ratio of the first slurry, the second slurry, the third slurry, and the fourth slurry in the seventh mixture can be 1:(0.5~1):(0.25~1):(0.25~1), preferably 1:(0.5~0.75):(0.25~0.75):(0.25~0.75). The above slurry ratio is beneficial to further improve the electrical performance of lithium iron phosphate materials.
[0050] Drying can be spray drying. Specifically, drying conditions may include: inlet temperature of 180~240℃, outlet temperature of 80~140℃, particle size D50 of 20~60μm, and moisture content ≤1.5wt%.
[0051] The third sintering can be carried out in the presence of a protective gas, which may include at least one of nitrogen and argon. Specifically, the conditions for the third sintering may include: carrying out the sintering under a nitrogen atmosphere at a temperature of 750-800°C for 4-8 hours. Further, lithium iron phosphate material can be obtained after the third sintering through an air jet milling step.
[0052] A second aspect of this disclosure provides lithium iron phosphate materials prepared by the method of the first aspect of this disclosure.
[0053] This lithium iron phosphate material comprises four particle sizes: large, medium, medium, and small, exhibiting a relatively continuous particle size distribution and quantity ratio. Specifically, particles with a diameter greater than 1 μm account for 1–3% of the total, particles with a diameter between 500 and 1000 nm account for 4–10%, particles with a diameter between 200 and 500 μm account for 15–30%, and particles with a diameter less than 200 nm account for 65–80%. In particular, particles with a diameter between 200 and 1000 nm exhibit higher sphericity and integrity, which helps ensure the stability of the gradation structure, achieving higher compaction density, specific capacity, and lower powder resistivity, thus improving electrochemical performance and long-term cycling stability. Specifically, the compaction density of this lithium iron phosphate material is 2.64 g / cm³. 3 The resistivity of the powder can be below 15 Ω·cm, preferably below 10 Ω·cm.
[0054] Using this lithium iron phosphate material to prepare lithium-ion batteries can significantly improve the energy density, rate performance, and cycle life of the batteries, which meets the development needs of high-end application markets such as long-range electric vehicles and high-efficiency energy storage systems, and has good prospects for industrial application.
[0055] A third aspect of this disclosure provides a lithium-ion battery, including the lithium iron phosphate material of the second aspect of this disclosure.
[0056] This disclosure does not impose any special limitations on the specific structure, packaging form, and manufacturing method of lithium-ion batteries. For example, a lithium-ion battery may include a positive electrode, a negative electrode, an electrolyte, and a separator. The positive electrode may include a positive current collector and a positive electrode material, and the positive electrode material may include the lithium iron phosphate material of the second aspect of this disclosure. The negative electrode may include a negative current collector and a negative electrode material (such as graphite). The electrolyte may be a carbonate-based electrolyte, and the separator may be a polyolefin separator. The packaging form of the lithium-ion battery may be a pouch battery, a square aluminum-cased battery, a blade aluminum-cased battery, etc. This lithium-ion battery has the same beneficial effects as described above, and will not be repeated here.
[0057] The present disclosure is further described in detail below through examples, but is not intended to limit the present disclosure. Unless otherwise specified, all raw materials used in the examples are commercially available.
[0058] In the examples, ferric hydroxyphosphate was prepared as follows: (1) Ferrous sulfate, phosphoric acid, and sodium hydroxide (precipitant) (byproducts of titanium dioxide) were mixed in a weight ratio of 1:(0.001~0.005):(0.005~0.007) and purified by pressure filtration to obtain a ferrous sulfate solution; (2) Add an appropriate amount of phosphoric acid to the ferrous sulfate solution to lower the pH value of the ferrous sulfate solution to 2~2.5; (3) Add hydrogen peroxide (concentration of 30~60 wt%), phosphoric acid, ammonium dihydrogen phosphate solution (concentration of 30 wt%) and ammonia (concentration of 28~29 wt%) to ferrous sulfate solution and react at 25~70℃ for 2~6h to form a mixed slurry. Wash the mixed slurry with water and filter it repeatedly to obtain the hydroxyferric phosphate precursor. The weight ratio of ferrous sulfate, hydrogen peroxide, phosphoric acid, ammonium dihydrogen phosphate and ammonia is 1000:145:78:332:91. (4) The above-mentioned hydroxyferric phosphate precursor was flash-dried at an inlet air temperature of 220±20℃ and an outlet air temperature of 110±10℃, and sintered at 530~560℃ for 4~5h under air conditions to obtain hydroxyferric phosphate.
[0059] Ti-doped ferric hydroxyphosphate was prepared by the following method: (1) Ferrous sulfate, phosphoric acid, and sodium hydroxide (precipitant) (byproducts of titanium dioxide) were mixed in a weight ratio of 1:(0.001~0.005):(0.005~0.007) and purified by pressure filtration to obtain a ferrous sulfate solution; (2) Add an appropriate amount of phosphoric acid to the ferrous sulfate solution to lower the pH value of the ferrous sulfate solution to 2~2.5; (3) Add TiO2, hydrogen peroxide (concentration of 30~60wt%), phosphoric acid, ammonium dihydrogen phosphate solution (concentration of 30wt%) and ammonia (concentration of 28~29wt%) to ferrous sulfate solution and react at 25~70℃ for 2~6h to form a mixed slurry. Wash the mixed slurry with water and filter it repeatedly to obtain the hydroxyferric phosphate precursor. The weight ratio of ferrous sulfate, TiO2, hydrogen peroxide, phosphoric acid, ammonium dihydrogen phosphate and ammonia is 1000:2:145:78:332:91. (4) The above-mentioned hydroxy ferric phosphate precursor was flash-dried in a flash evaporator at an inlet air temperature of 220±20℃ and an outlet air temperature of 110±10℃, and sintered at 530~560℃ for 4~5h under air conditions to obtain Ti-doped hydroxy ferric phosphate.
[0060] The microstructure of lithium iron phosphate materials was examined using a Zeiss Sigma 360 scanning electron microscope under the following conditions: voltage 10 kV, magnification 20 kV. Particle size distribution was statistically analyzed using a Nano Measurer; carbon content and metal element content were determined using a carbon-sulfur analyzer.
[0061] Example 1 S1. 4000g of ferric hydroxyphosphate (Fe / P = 1.43, BET specific surface area = 30m²) 21230g of lithium phosphate and 3.1g of lithium carbonate were mixed, and 43.3g of manganese acetate, 7.56g of ammonium metavanadate, 137.6g of glucose, 91.7g of polyethylene glycol and 8300g of deionized water were added to form a dispersion in a ball mill. The dispersion was then transferred to a sand mill and ground at 20℃, with a particle size D50 of 0.8μm and a solid content of 40wt%. The resulting slurry was spray-dried, with the inlet air temperature controlled at 210℃ and the outlet air temperature controlled at 110℃, resulting in a granulation D50 of 40μm and a moisture content ≤1.5wt%. The resulting precursor powder was calcined at 820℃ for 7h under a nitrogen atmosphere. The sintered material was then pulverized to obtain the first precursor (P / Fe / Li ratio of 1:0.96:0.989, carbon content of 0.2wt%, manganese content of 0.3wt%, and vanadium content of 0.1wt%).
[0062] S2. 4000g of Ti-doped ferric hydroxyphosphate (Fe / P ratio 1.47, BET specific surface area 65m²) 2 A mixture of 1203.7 g lithium phosphate and 61.7 g lithium carbonate (containing 0.23 wt% Ti), along with 30.6 g titanium dioxide, 137.6 g glucose, 91.7 g polyethylene glycol, and 8300 g deionized water, was prepared in a ball mill to form a dispersion. The dispersion was then transferred to a sand mill and ground at 20°C, with a particle size D50 of 0.3 μm and a solid content of 40 wt%. The resulting slurry was spray-dried, with an inlet air temperature of 210°C and an outlet air temperature of 110°C, achieving a particle size D50 of 40 μm and a moisture content ≤1.5 wt%. The resulting precursor powder was calcined at 650°C for 4 hours under a nitrogen atmosphere. The sintered material was then pulverized to obtain a second precursor (P / Fe / Li ratio of 1:0.985:1.034, carbon content of 0.2 wt%, and titanium content of 0.6 wt%).
[0063] S3. Mix 4000g of the first precursor, 120g of polyvinylpyrrolidone, 40g of glucose and 6000g of deionized water to form a dispersion; transfer the dispersion to a sand mill and grind it at a temperature of 20℃, a particle size D50 of 1.2μm and a solid content of 40wt% to obtain a first slurry with a particle size of 1.2μm.
[0064] S4. Mix 4000g of the first precursor, 120g of polyvinylpyrrolidone, 40g of glucose and 6000g of deionized water to form a dispersion; transfer the dispersion to a sand mill and grind it at a temperature of 20℃, a particle size D50 of 0.6μm and a solid content of 40wt% to obtain a second slurry with a particle size of 0.6μm.
[0065] S5. Mix 4000g of the second precursor, 120g of polyvinylpyrrolidone, 40g of glucose and 6000g of deionized water to form a dispersion; transfer the dispersion to a sand mill and grind it at a temperature of 20℃, a particle size D50 of 0.35μm and a solid content of 40wt% to obtain a third slurry with a particle size of 0.35μm.
[0066] S6. Mix 4000g of the second precursor, 120g of polyvinylpyrrolidone, 40g of glucose and 6000g of deionized water to form a dispersion; transfer the dispersion to a sand mill and grind it at a temperature of 20℃, a particle size D50 of 0.15μm and a solid content of 40wt% to obtain a fourth slurry with a particle size of 0.15μm.
[0067] S7. Mix the first, second, third, and fourth slurries in a weight ratio of 3:3:2:2 for 1 hour. Spray dry the resulting slurry, controlling the inlet air temperature at 210℃ and the outlet air temperature at 110℃, achieving a granulation D50 of 40μm and a moisture content ≤1.5wt%. Calcinate the resulting powder at 780℃ for 6 hours under a nitrogen atmosphere. Pulverize the sintered material to obtain lithium iron phosphate material with a carbon content of 1.3wt%. See electron micrograph for details. Figure 1 As shown, the lithium iron phosphate material has a dense packing structure formed by four-fold particle size distribution particles, of which the number of particles with a particle size distribution of more than 1000 nm accounts for 2%, the number of particles with a particle size distribution of 500~1000 nm accounts for 7%, the number of particles with a particle size distribution of 200~500 nm accounts for 20%, and the number of particles with a particle size distribution of less than 200 nm accounts for 71%.
[0068] Example 2 S1. 4000g of ferric hydroxyphosphate (Fe / P = 1.40, BET specific surface area = 4m²) 2 1221.6g of lithium phosphate and 39.2g of lithium carbonate were mixed, and 29.02g of manganese acetate, 15.2g of ammonium metavanadate, 184.3g of polyethylene glycol, 115.2g of citric acid and 5500g of deionized water were added to form a dispersion in a ball mill. The dispersion was then transferred to a sand mill and ground at 10℃, a particle size D50 of 0.9μm and a solid content of 50wt%. The resulting slurry was then spray-dried. The inlet air temperature was controlled at 180℃, the outlet air temperature at 80℃, the granulation D50 was 60μm, and the moisture content was ≤1.5wt%. The obtained precursor powder was calcined at 840℃ for 4 hours under nitrogen atmosphere. The sintered material was then pulverized to obtain the first precursor (P / Fe / Li ratio of 1:0.950:0.998, carbon content of 0.1wt%, manganese content of 0.2wt%, and vanadium content of 0.2wt%).
[0069] S2. 4000g of Ti-doped ferric hydroxyphosphate (Fe / P = 1.50, BET specific surface area = 100m²) 2 1207.6 g of lithium phosphate and 6.4 g of phosphoric acid were mixed, and 38.6 g of titanium dioxide, 184.9 g of polyethylene glycol, 115.6 g of citric acid and 5500 g of deionized water were added to form a dispersion in a ball mill. The dispersion was then transferred to a sand mill and ground at 10 °C, with a particle size D50 of 0.2 μm and a solid content of 50 wt%. The resulting slurry was spray-dried, with the inlet air temperature controlled at 180 °C and the outlet air temperature controlled at 80 °C, resulting in a particle size D50 of 60 μm and a moisture content ≤1.5 wt%. The resulting precursor powder was calcined at 700 °C for 3 h under a nitrogen atmosphere. The sintered material was then pulverized to obtain a second precursor (P / Fe / Li ratio of 1:1:1.03, carbon content of 0.1 wt%, and titanium content of 0.6 wt%).
[0070] S3. Mix 4000g of the first precursor, 80g of polyvinylpyrrolidone, 60g of sucrose and 4000g of deionized water to form a dispersion; transfer the dispersion to a sand mill and grind it at a temperature of 10℃, a particle size D50 of 1.0μm and a solid content of 50wt% to obtain a first slurry with a particle size of 1.0μm.
[0071] S4. Mix 4000g of the first precursor, 80g of polyvinylpyrrolidone, 60g of sucrose and 4000g of deionized water to form a dispersion; transfer the dispersion to a sand mill and grind it at a temperature of 10℃, a particle size D50 of 0.5μm and a solid content of 50wt% to obtain a second slurry with a particle size of 0.5μm.
[0072] S5. Mix 4000g of the second precursor, 80g of polyvinylpyrrolidone, 60g of sucrose and 4000g of deionized water to form a dispersion; transfer the dispersion to a sand mill and grind it at a temperature of 10℃, a particle size D50 of 0.3μm and a solid content of 50wt% to obtain a third slurry with a particle size of 0.3μm.
[0073] S6. Mix 4000g of the second precursor, 80g of polyvinylpyrrolidone, 60g of sucrose and 4000g of deionized water to form a dispersion; transfer the dispersion to a sand mill and grind it at a temperature of 10℃, a particle size D50 of 0.1μm and a solid content of 50wt% to obtain a fourth slurry with a particle size of 0.1μm.
[0074] S7. Mix the first, second, third, and fourth slurries in a weight ratio of 4:3:2:1 for 1 hour. Spray dry the resulting slurry, controlling the inlet air temperature at 180℃ and the outlet air temperature at 80℃, achieving a granulation D50 of 60μm and a moisture content ≤1.5wt%. Calcinate the resulting powder at 800℃ for 4 hours under a nitrogen atmosphere. Pulverize the sintered material to obtain lithium iron phosphate material with a carbon content of 1.1wt%. Electron micrographs and... Figure 1 Similarly, the proportion of particles with a diameter greater than 1000nm was 3%, the proportion of particles with a diameter between 500 and 1000nm was 7%, the proportion of particles with a diameter between 200 and 500nm was 22.5%, and the proportion of particles with a diameter between 200nm was 67.5%.
[0075] Example 3 S1. 4000g of ferric hydroxyphosphate (Fe / P = 1.46, BET specific surface area = 50m²) 2 1248.6g of lithium phosphate and 13.8g of lithium carbonate were mixed, and 58.0g of manganese acetate, 138.2g of polyethylene glycol, 92.1g of sucrose and 12730g of deionized water were added to form a dispersion in a ball mill. The dispersion was then transferred to a sand mill and ground at 30℃, with a particle size D50 of 0.7μm and a solid content of 30%wt%. The resulting slurry was spray-dried, with the inlet air temperature controlled at 240℃ and the outlet air temperature at 140℃, resulting in a granulation D50 of 20μm and a moisture content ≤1.5wt%. The resulting precursor powder was calcined at 800℃ for 10h under a nitrogen atmosphere. The sintered material was then pulverized to obtain the first precursor (P / Fe / Li ratio of 1:0.970:1.019, carbon content of 0.3wt%, and manganese content of 0.4wt%).
[0076] S2. 4000g of Ti-doped ferric hydroxyphosphate (Fe / P ratio 1.44, BET specific surface area 30m²) 2A mixture of 1215.0 g lithium phosphate and 22.7 g lithium carbonate (containing 0.34 wt% Ti), along with 23.1 g titanium dioxide, 138.2 g polyethylene glycol, 92.1 g sucrose, and 12870 g deionized water, was prepared in a ball mill to form a dispersion. The dispersion was then transferred to a sand mill and ground at 30°C, with a particle size D50 of 0.4 μm and a solid content of 30 wt%. The resulting slurry was spray-dried, with an inlet air temperature of 240°C and an outlet air temperature of 140°C, achieving a particle size D50 of 20 μm and a moisture content ≤1.5 wt%. The resulting precursor powder was calcined at 600°C for 5 hours under a nitrogen atmosphere. The sintered material was then pulverized to obtain a second precursor (P / Fe / Li ratio of 1:0.970:1.047, carbon content of 0.3 wt%, and titanium content of 0.6 wt%).
[0077] S3. Mix 4000g of the first precursor, 120g of polyvinylpyrrolidone, 100g of polyethylene glycol and 9300g of deionized water to form a dispersion; transfer the dispersion to a sand mill and grind it at a temperature of 10℃, a particle size D50 of 1.4μm and a solid content of 30wt% to obtain a first slurry with a particle size of 1.4μm.
[0078] S5. Mix 4000g of the second precursor, 120g of polyvinylpyrrolidone, 100g of polyethylene glycol and 9300g of deionized water to form a dispersion; transfer the dispersion to a sand mill and grind it at a temperature of 10℃, a particle size D50 of 0.7μm and a solid content of 30wt% to obtain a second slurry with a particle size of 0.7μm.
[0079] S6. Mix 4000g of the second precursor, 120g of polyvinylpyrrolidone, 100g of polyethylene glycol and 9300g of deionized water to form a dispersion; transfer the dispersion to a sand mill and grind it at a temperature of 10℃, a particle size D50 of 0.4μm and a solid content of 30wt% to obtain a third slurry with a particle size of 0.4μm.
[0080] S7. Mix 4000g of the third precursor, 120g of polyvinylpyrrolidone, 100g of polyethylene glycol and 9300g of deionized water to form a dispersion; transfer the dispersion to a sand mill and grind it at a temperature of 10℃, a particle size D50 of 0.2μm and a solid content of 30wt% to obtain a fourth slurry with a particle size of 0.2μm.
[0081] S8. Mix the first, second, third, and fourth slurries in a weight ratio of 4:2:2:2 for 1 hour. Spray dry the resulting slurry, controlling the inlet air temperature at 240℃ and the outlet air temperature at 140℃, achieving a granulation D50 of 20μm and a moisture content ≤1.5wt%. Calcinate the resulting powder at 750℃ for 8 hours under a nitrogen atmosphere. Pulverize the sintered material to obtain lithium iron phosphate material with a carbon content of 1.5wt%. Electron micrographs and... Figure 1 Similarly, the proportion of particles with a diameter greater than 1000nm was 2.5%, the proportion of particles with a diameter between 500 and 1000nm was 6%, the proportion of particles with a diameter between 200 and 500nm was 23.5%, and the proportion of particles with a diameter less than 200nm was 68%.
[0082] Example 4 Lithium iron phosphate material was prepared according to the method of Example 1, except that in step S1, 30.6g of titanium dioxide was used instead of manganese acetate and ammonium metavanadate. In the prepared lithium iron phosphate material, the proportion of particles with a particle size distribution of more than 1000nm was 1%, the proportion of particles with a particle size distribution of 500~1000nm was 9%, the proportion of particles with a particle size distribution of 200~500nm was 25%, and the proportion of particles with a particle size distribution of less than 200nm was 65%.
[0083] Example 5 Lithium iron phosphate material was prepared according to the method of Example 1, except that in step S1, the manganese content of the first precursor was 0.1 wt% and the vanadium content was 0.1 wt%, and in step S2, the titanium content of the second precursor was 0.1 wt%. In the prepared lithium iron phosphate material, the proportion of particles with a particle size distribution of more than 1000 nm was 3%, the proportion of particles with a particle size distribution of 500~1000 nm was 9%, the proportion of particles with a particle size distribution of 200~500 nm was 21%, and the proportion of particles with a particle size distribution of less than 200 nm was 67%.
[0084] Example 6 The lithium iron phosphate material was prepared according to the method of Example 1, except that in step S7, the weight ratio of the first slurry, the second slurry, the third slurry, and the fourth slurry was 2.5:2.5:2.5:2.5. In the prepared lithium iron phosphate material, the proportion of particles with a particle size distribution of more than 1000 nm was 1.5%, the proportion of particles with a particle size distribution of 500~1000 nm was 5%, the proportion of particles with a particle size distribution of 200~500 nm was 18%, and the proportion of particles with a particle size distribution of less than 200 nm was 75.5%.
[0085] Comparative Example 1 Lithium iron phosphate material was prepared according to the method of Example 1, except that in step S2, 4000g of hydroxyferric phosphate (Fe / P = 1.47, BET specific surface area = 65m²) was used. 2 In the lithium iron phosphate material prepared by replacing Ti-doped hydroxyl iron phosphate with / g), the proportion of particles with a particle size distribution above 1000nm is 2.5%, the proportion of particles with a particle size distribution between 500 and 1000nm is 13%, the proportion of particles with a particle size distribution between 200 and 500nm is 32%, and the proportion of particles with a particle size distribution below 200nm is 52.5%.
[0086] Comparative Example 2 Lithium iron phosphate material was prepared according to the method of Example 1, except that in step S1, 4000g of iron phosphate (Fe / P = 0.960, BET specific surface area = 10m²) was used. 2 In step S2, 4000g of ferric phosphate (Fe / P = 0.985, BET specific surface area = 20m²) is used to replace hydroxyferric phosphate. 2 In the lithium iron phosphate material prepared by replacing Ti-doped hydroxyl iron phosphate with / g), the proportion of particles with a particle size distribution of more than 1000 nm is 2%, the proportion of particles with a particle size distribution of 500~1000 nm is 9%, the proportion of particles with a particle size distribution of 200~500 nm is 40%, and the proportion of particles with a particle size distribution of 200 nm is 49%.
[0087] Comparative Example 3 The lithium iron phosphate material was prepared according to the method of Example 1, except that in step S7, the first slurry, the third slurry, and the fourth slurry were mixed in a weight ratio of 6:2:2, that is, the second slurry was not added. In the prepared lithium iron phosphate material, the number of particles with a particle size distribution of more than 1000 nm accounted for 7%, the number of particles with a particle size distribution of 500~1000 nm accounted for 6%, the number of particles with a particle size distribution of 200~500 nm accounted for 25%, and the number of particles with a particle size distribution of less than 200 nm accounted for 62%.
[0088] Test Case The lithium iron phosphate materials of the examples and comparative examples were subjected to compaction density tests and assembled into batteries to test their electrical performance. The results are listed in Table 1.
[0089] The test method for compaction density is as follows: Weigh 1g of lithium iron phosphate material sample into a compaction mold, place it into the compaction equipment and start the test. The powder compaction density result is taken as the result under 30KN pressure.
[0090] The powder resistivity is tested using the four-probe method.
[0091] The battery assembly method is as follows: Lithium iron phosphate material, Super-P and PVDF are dispersed in NMP at a weight ratio of 80:10:10. After ball milling and uniform dispersion, the mixture is coated on aluminum foil and vacuum dried to obtain the positive electrode sheet. The electrolyte is 1 mol / L LiPF6, with a solvent volume ratio of EC:DMC:EMC = 1:1:1. The separator is Celgard polypropylene membrane, and the lithium metal sheet is the negative electrode. Together, they are assembled into a coin cell.
[0092] The initial discharge capacity test method is as follows: the test voltage range is 2.0~3.75V. Charge to 3.75V using constant current and constant voltage charging, and discharge to 2.0V using constant current discharging. The charge and discharge current is 0.1C for 1 cycle. Then charge and discharge at 1C for 3 cycles. The cutoff voltage condition is the same as 0.1C.
[0093] Table 1
[0094] As shown in Table 1, the lithium iron phosphate material prepared in the examples has higher compaction density and lower resistivity, and exhibits superior electrical performance for lithium-ion batteries.
[0095] The preferred embodiments of this disclosure have been described in detail above with reference to the accompanying drawings. However, this disclosure is not limited to the specific details of the above embodiments. Within the scope of the technical concept of this disclosure, various simple modifications can be made to the technical solutions of this disclosure, and these simple modifications all fall within the protection scope of this disclosure.
[0096] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, this disclosure will not describe the various possible combinations separately.
[0097] In addition, the various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A method for preparing lithium iron phosphate material, characterized in that, The method includes: The first mixture containing the first iron phosphorus source, the first lithium phosphorus source, the first metal dopant and the first carbon source is wet-milled, dried and then sintered to obtain the first precursor. The second mixture containing the second iron phosphorus source, the second lithium phosphorus source, the second metal dopant, and the second carbon source is wet-milled, dried, and then subjected to a second sintering to obtain the second precursor. The third mixture containing the first precursor and the third carbon source is wet-milled to obtain a first slurry with a first particle size. The fourth mixture containing the first precursor and the fourth carbon source is wet-milled to obtain a second slurry with a second particle size. The fifth mixture containing the second precursor and the fifth carbon source is wet-milled to obtain a third slurry with a third particle size. The sixth mixture containing the second precursor and the sixth carbon source is wet-milled to obtain a fourth slurry with a fourth particle size. The seventh mixture containing the first slurry, the second slurry, the third slurry, and the fourth slurry is dried and then subjected to a third sintering to obtain lithium iron phosphate material; Wherein, the first iron phosphorus source is hydroxyferric phosphate, and the second iron phosphorus source is hydroxyferric phosphate containing metal doping elements; the first particle size, the second particle size, the third particle size, and the fourth particle size decrease sequentially.
2. The method according to claim 1, wherein, The first phosphorus-iron source has an iron-to-phosphorus molar ratio of 1.40 to 1.46 and a BET specific surface area of 4 to 50 m². 2 / g.
3. The method according to claim 1, wherein, The second phosphorus-iron source has an iron-to-phosphorus molar ratio of 1.44 to 1.50 and a BET specific surface area of 30 to 100 m². 2 / g.
4. The method according to claim 1, wherein, The metal doping element includes at least one of Ti, Nb, V, Mn, Mg, Ni and Zr.
5. The method according to claim 1, wherein, Based on the total weight of the second phosphorus iron source, the content of the metal doping element in the second phosphorus iron source is 0.1~0.4wt%.
6. The method according to claim 1, wherein, The first lithium phosphorus source and the second lithium phosphorus source each independently include at least one of lithium phosphate, lithium hydrogen phosphate, and lithium dihydrogen phosphate; The first metal dopant includes at least one of manganese dopant, vanadium dopant, nickel dopant, and zirconium dopant; The second metal dopant includes at least one of titanium dopant, niobium dopant, and magnesium dopant; The first carbon source, the second carbon source, the third carbon source, the fourth carbon source, the fifth carbon source, and the sixth carbon source each independently include at least one of glucose, sucrose, polyethylene glycol, citric acid, polyvinylpyrrolidone, and starch.
7. The method according to claim 6, wherein, The first metal dopant includes at least one of manganese acetate, ammonium metavanadate, nickel oxide, and zirconium oxide; The second metal dopant includes at least one of titanium dioxide, niobium oxide, and magnesium acetate.
8. The method according to claim 1, wherein, The first mixture further contains a first supplement, and the second mixture further contains a second supplement; The first supplement and the second supplement each independently comprise at least one of phosphoric acid, ammonium dihydrogen phosphate, lithium carbonate, lithium hydroxide, lithium acetate, and lithium oxalate.
9. The method according to claim 1, wherein, Based on the total weight of the first precursor, the carbon content of the first precursor is 0.1~0.3wt%, and the metal doping content is 0.1~0.5wt%. Based on the total weight of the second precursor, the carbon content of the second precursor is 0.1~0.3wt%, and the metal doping content is 0.1~0.7wt%.
10. The method according to claim 1, wherein, In the third mixture, the weight ratio of the first precursor to the third carbon source is 1000:(30~60). In the fourth mixture, the weight ratio of the first precursor to the fourth carbon source is 1000:(30~60). In the fifth mixture, the weight ratio of the second precursor to the fifth carbon source is 1000:(30~60). In the sixth mixture, the weight ratio of the second precursor to the sixth carbon source is 1000:(30~60).
11. The method according to claim 1, wherein, The first particle size is 1.0~2.0μm, the second particle size is 0.5~1.0μm, the third particle size is 0.2~0.5μm, and the fourth particle size is 0.1~0.2μm; And / or, In the seventh mixture, the weight ratio of the first slurry, the second slurry, the third slurry and the fourth slurry is 1:(0.5~1):(0.25~1):(0.25~1).
12. The method according to claim 1, wherein, The conditions for the first sintering include: a temperature of 800~840℃ and a time of 4~10h; The conditions for the second sintering include: a temperature of 600~700℃ and a time of 3~5h; The conditions for the third sintering include: a temperature of 750~800℃ and a time of 4~8h.
13. The lithium iron phosphate material prepared by the method according to any one of claims 1 to 12.
14. A lithium-ion battery, characterized in that, Including the lithium iron phosphate material as described in claim 13.
Citation Information
Patent Citations
Preparation method of high-energy-density lithium iron phosphate material
CN115650200A
High-compaction graded lithium iron phosphate as well as preparation method and application thereof
CN118419889A
Method for preparing high-compaction lithium iron phosphate material from hydroxyl iron phosphate and application of high-compaction lithium iron phosphate material
CN119528106A
Preparation method and application of iron phosphate material
CN120004235A
Preparation method for lithium iron phosphate cathode material and lithium battery
US12252400B1
Cited By
Composite sodium iron phosphate positive electrode material, preparation method thereof, positive electrode and sodium ion battery
CN122540838A